Impact of early division of the middle cerebral artery on outcome following mechanical thrombectomy. Issue 4 (August 2020) - Styczen, Hanna; Maus, Volker; Hesse, Amélie C; Goertz, Lukas; Fischer, Sebastian; Riedel, Christian; Forsting, Michael; Radbruch, Alexander; Behme, Daniel
Background: Mechanical thrombectomy has become the standard care for acute ischemic stroke caused by large vessel occlusion. However, complete reperfusion cannot be achieved in all cases, and several factors influencing the results of mechanical thrombectomy have been investigated. Among others, a tortuous anatomy is associated with lower rates of complete reperfusion. We aimed to investigate whether an early division of the middle cerebral artery has an impact on reperfusion results in mechanical thrombectomy. Methods: Retrospective review of consecutive patients with M1 occlusion treated endovascularly between January 2016 and December 2019 at three tertiary care centers. The study group was dichotomized based on the length of the M1 segment. Early division of the middle cerebral artery was defined as a maximum length of 10 mm of the M1 segment. Primary endpoints were first-pass mTICI scores of 3, ≥2c, and ≥2b. Secondary endpoints contained final reperfusion, number of device-passes, time interval from groin puncture to reperfusion, rate of postinterventional symptomatic intracranial hemorrhage, and frequency of emboli of new territory. Results: Among 284 included patients, 70 presented with an early division of the M1 segment (25%). Reperfusion results did not differ significantly between early and late division of M1. A higher rate of symptomatic intracranial hemorrhage was found in the group with an early M1 division treated with aspiration only (14.3% vs. 0%; p = 0.013). Patients with late M1 division had a significantly higher rate of large artery sclerosis (19.2% vs. 8.6%, p = 0.039). Conclusion: The anatomic variant of an early division of the middle cerebral artery was not a predictor for incomplete reperfusion.